Healthcare Access of Autistic Language Minorities: The Case of English Official Language Minorities in Quebec, Canada - Amantayev, Nariman; Rao, Sabrina; Nadig, Aparna (Linguistic Minorites and Society / Minorités linguistiques et société, 2025)
Abstract English and French are both official languages in Canada. Whereas official language minorities (English speakers in Quebec, French speakers in the rest of Canada) face healthcare barriers and poor health outcomes, autistic individuals and their families also struggle with accessing healthcare. We examined healthcare access at the intersection of these groups: the autistic community, including English minority-language speakers from Quebec, French majority-language speakers from Quebec, and English majority-language speakers from elsewhere in Canada (n = 165). Linguistic minorities reported poorer access to publicly-funded services and lower satisfaction that their language needs were being met than did linguistic majorities. Foreign-born English speakers also experienced poorer access than their Canadian-born counterparts. These preliminary findings suggest that autistic language minorities face known barriers to accessing healthcare, potentially at a higher rate than that experienced by language minorities in general. Résumé L’anglais et le français sont les langues officielles du Canada. Les minorités de langue officielle (anglophones au Québec, francophones hors Québec) font face à des obstacles en matière de santé, tout comme les personnes autistes et leurs familles. Nous avons examiné l’accès aux services de santé à l’intersection de ces groupes : la communauté autiste, incluant des anglophones (minoritaires) et francophones (majoritaires) du Québec, ainsi que des anglophones (majoritaires) du reste du Canada (n = 165). Les minorités linguistiques déclarent un accès plus difficile aux services de santé publics et une moindre satisfaction quant à la prise en compte de leurs besoins linguistiques, comparativement aux majorités linguistiques. Les anglophones nés à l’étranger rapportent également un accès plus difficile que leurs pairs nés au Canada. Ces résultats préliminaires suggèrent que les minorités linguistiques autistes font face à des obstacles connus en matière d’accès aux soins, possiblement à un degré plus élevé.

Stillbirth in an Anglophone minority of Canada - Auger, Nathalie; Daniel, Mark; Mortensen, Laust; Toa-Lou, Clarisse; Costopoulos, André (International Journal of Public Health, 2015)
Objectives We assessed trends in stillbirth over time for Francophones and Anglophones of Quebec, a large Canadian province with publically funded health care and an English-speaking minority. Methods We calculated stillbirth rates for Francophones and Anglophones, and estimated hazard ratios (HR) by decade from 1981 to 2010, adjusting for maternal characteristics. We analyzed temporal trends by gestational interval and cause of fetal death. Results Stillbirth rates decreased in Quebec during the three decades, due to improved rates in Francophones. Rates decreased for Anglophones in 1991–2000, but increased in 2001–2010 at term, during the second trimester, and for most causes of fetal death. In the 2000s, the hazard of stillbirth for Anglophones was nearly the same as the hazard for Francophones in the 1980s (HR 0.93, 95 % confidence interval 0.82, 1.05). Conclusions Stillbirth rates declined in both Francophones and Anglophones before the turn of the century, but increased thereafter for Anglophones, suggesting that linguistic inequalities in stillbirth may be emerging in Quebec. Linguistic status may be a useful marker for surveillance of inequalities in stillbirth.

Contribution of local area deprivation to cultural-linguistic inequalities in foetal growth restriction: Trends over time in a Canadian metropolitan centre - Auger, Nathalie; Park, Alison L.; Daniel, Mark (Health & Place, 2013)
This study investigated temporal trends in heterogeneity of foetal growth restriction across neighbourhood deprivation levels for two culturally distinct communities (Anglophones and Francophones) in a North American metropolitan centre. Inequalities in foetal growth restriction related to deprivation fell from 1989 to 2008 for Francophones, but initial improvements for Anglophones later reversed with a rise in poor foetal growth in the most materially disadvantaged and, unexpectedly, advantaged areas as well. Inequalities in foetal growth restriction related to neighbourhood material deprivation may be emerging in this minority Anglophone population. Potential mechanisms underlying these trends are discussed, as well as implications for perinatal health policy.

Francophone and Anglophone perinatal health: Temporal and regional inequalities in a Canadian setting, 1981-2008 - Auger, Nathalie; Park, Alison L.; Harper, Sam (Francophone and Anglophone perinatal health: Temporal and regional inequalities in a Canadian setting, 2012)
Objectives We evaluated temporal and regional inequalities in adverse birth outcomes between Anglophones and Francophones of a Canadian province. Methods Odds ratios and rate differences in preterm birth (PTB, <37 gestational weeks) and small-for-gestational-age (SGA) birth were computed for Anglophones relative to Francophones for singleton live births in Québec from 1981 to 2008 (N = 2,292,237), adjusting for maternal characteristics. Trends over time and residential region were evaluated. Results Rates of PTB and SGA birth overall were lower for Anglophones relative to Francophones, but temporal and regional trends varied by outcome. Although PTB rates increased over time, inequalities between Francophones and Anglophones were relatively stable. In contrast, inequalities in SGA birth narrowed over time as Francophone rates declined more than Anglophones. Inequalities in SGA birth favored Anglophones overall, but the gap gradually reversed in Montréal (the largest metropolitan center) to currently favor Francophones. Conclusions PTB and SGA birth rates favored Anglophones over Francophones. The linguistic gap was generally stable over time for PTB, but narrowed or reversed for SGA birth. Language may be used to capture inequalities in perinatal health in countries where different linguistic groups predominate.

Social service accessibility in Montreal’s English-speaking disability community: A needs-based assessment - Nash, Aubrey (McGill University, 2019)
Health and social service systems can be difficult to traverse, especially in the stressful situations that often necessitate accessing them. In Quebec, these difficulties are exacerbated for English speaking or limited French-proficient persons. This thesis employs a needs-based assessment to explore how linguistic-based access barriers to health and social services affect Montreal’s English-speaking Disability community, focusing on those with intellectual and/or developmental disabilities and their caregivers/advocates. It identifies the community’s needs and proposes three key issues that result in the needs being unmet by the social service system. Specifically, the issues are (i) inaccessible information for limited French-proficient persons, as many important documents are available in only French; (ii) the primary method for bolstering language congruency between service users and providers relies on the service seeker to acquire French, which is incompatible with the lived experiences of many members of the Disability community; (iii) limited options for English services across Montreal. This thesis indicates the protection of the French language under the Charter of the French Language (1977) impacts the ability of the Act Respecting Health Services and Social Services (1991) to protect the rights of English-speaking Quebeckers to receive services in English. Through a human rights model of Disability and citizenship lens, it suggests that language laws can be understood and implemented to protect the Quebecois identity while ensuring active inclusion of otherwise marginalized communities in health and social service systems

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Portrait de la prématurité et des naissances ayant un faible poids pour l’âge gestationnel dans les communautés linguistiques au Québec, 1989 à 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, M.; Auger, Marianne (Institut national de santé publique du Québec, 2018)

Portrait of preterm and small-for-gestational-age births by linguistic community in Québec, 1989 to 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, Marianne; Auger, Nathalie (Institut national de santé publique du Québec, 2018)